Global Perspectives in Early Childhood Education Diversity, Challenges and Possibilities - Liimets, Airi; Veisson, Marika; Hujala, Eeva; Smith, Peter K.; Waniganayake, Manjula (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2012)
The idea for this book arose from presentations delivered at two conferences in Tartu and in Tallinn in Estonia. These conferences brought together many professionals and researchers working in early education, many from Europe, and also Australia and the USA. This book, written by 37 authors, consists of chapters about the development of early childhood education, children's developing skills and the early childhood curriculum, and about the role of early childhood teachers. Further topics are the role of parents in early childhood education, and the work with children with special needs in the preschool. The book will be of interest to those interested in early childhood practice and policy.
Keywords: předškolní výchova; děti předškolního věku; preschool education; preschool children; elektronické knihy; electronic books